Justice and identity : the 'non-Jewish Jew', cosmopolitanism and anti-apartheid activism in twentieth century South Africa - Pugh-Jones, Alana Frances (Department of Political Studies, 2014)
Includes abstract. Includes bibliographical references (leaves 88-90).